Antimicrobial activity of de novo designed cationic peptides against multi-resistant clinical isolates - Faccone, Diego (2014)
Fil: Faccone, Diego. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Servicio Antimicrobianos; Argentina.